Preparation of Sago Bark-Derived Magnetic Adsorbent by Impregnation and Carbonation for Lead and Copper Ions Removal - Soh-Fong, Lim; Nur Amalina Naimah, Hamidon; Sukinah, Binti Abdul Karim; David Chua, S.N.; Lim, Bee Huah (Trans Tech Publications Ltd, Switzerland, 2021)
This paper presents an alternative utilisation of sago barks from the sago industry. In this study, a sago bark-derived magnetic adsorbent was developed by impregnation with ferric chloride hexahydrate (FeCl3H2O) and carbonisation method. The potential of the sago bark-derived magnetic adsorbent to remove lead ion (Pb2+) and copper ion (Cu2+) from aqueous solution was assessed in a batch system. Adsorption experiments were performed as a function of initial concentration (5.0 – 15.0 mg/L). The magnetic adsorbent displayed good ferromagnetic property which aids the separation of the adsorbent after the decontamination process. The magnetic adsorbent was characterised by Fourier Transform Infrared (FTIR) Spectroscopy and Scanning Electron Microscopy embedded with an Energy Dispersive X-ray Spectrometer (SEM-EDX). The FT-IR spectra analysis revealed the surface functional groups of the magnetic adsorbent are C−O−C, C−OH, C− H, −C−C−O, Fe-O, O-H, and C-O. The maximum monolayer adsorption capacities were discovered to be 172.414 and 12500 mg/g for lead and copper ions, respectively. The batch adsorption isotherms were analysed using Langmuir, Freundlich, Jovanovic and Temkin isotherm models. The experimental data perfectly fitted with Langmuir isotherm modelling. The results indicated that the sago bark-derived magnetic adsorbent potentially to be an alternative in replacing more high-priced adsorbents for its application in heavy metal ions removal.